2020
DOI: 10.1302/2058-5241.5.190032
|View full text |Cite
|
Sign up to set email alerts
|

‘Frozen shoulder’ is ill-defined. How can it be described better?

Abstract: Frozen shoulder, a common and debilitating shoulder complaint, has been the subject of uncertainty within the scientific literature and clinical practice. We performed an electronic PubMed search on all (1559) articles mentioning ‘frozen shoulder’ or ‘adhesive capsulitis’ to understand and qualify the range of naming, classification and natural history of the disease. We identified and reviewed six key thought leadership papers published in the past 10 years and all (24) systematic reviews published on frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…3 POSS was recorded as an AE of the deep soft tissue event group when accompanied by restricted passive ROM with or without pain experienced for more than 12 weeks exceeding normal postoperative pain or stiffness and thus labeled by the operating surgeons either as capsulitis, frozen shoulder, or adverse shoulder stiffness. 1 Involved surgeons reported that their decision for treatment of POSS was mainly driven by severe shoulder pain at rest, notably at night, associated with passive motion limitation in abduction or flexion, and external rotation with the elbow at the body side. Additional treatments for POSS, including pain medication, physical therapy, corticoid infiltration, or a new surgical intervention (capsule release) were documented, and the severity of each POSS event was categorized according to an adapted version of the Clavien-Dindo classification, 18 which ranges from grade 1 (event not requiring pharmacological treatment or surgical, endoscopic, and radiological intervention) to grade 5 (event leading to death).…”
Section: Methodsmentioning
confidence: 99%
“…3 POSS was recorded as an AE of the deep soft tissue event group when accompanied by restricted passive ROM with or without pain experienced for more than 12 weeks exceeding normal postoperative pain or stiffness and thus labeled by the operating surgeons either as capsulitis, frozen shoulder, or adverse shoulder stiffness. 1 Involved surgeons reported that their decision for treatment of POSS was mainly driven by severe shoulder pain at rest, notably at night, associated with passive motion limitation in abduction or flexion, and external rotation with the elbow at the body side. Additional treatments for POSS, including pain medication, physical therapy, corticoid infiltration, or a new surgical intervention (capsule release) were documented, and the severity of each POSS event was categorized according to an adapted version of the Clavien-Dindo classification, 18 which ranges from grade 1 (event not requiring pharmacological treatment or surgical, endoscopic, and radiological intervention) to grade 5 (event leading to death).…”
Section: Methodsmentioning
confidence: 99%
“…Recovery from FSCS remains controversial in the literature. FSCS is sometimes reported as self-limiting pathology, or that need of care 10 , 11 and the time for symptoms resolution ranged from few months to two years. 10 , 12 , 13 Moreover, although some patients report complete symptom resolution, others report residual range of motion impairments and pain.…”
Section: Introductionmentioning
confidence: 99%
“…FSCS is sometimes reported as self-limiting pathology, or that need of care 10 , 11 and the time for symptoms resolution ranged from few months to two years. 10 , 12 , 13 Moreover, although some patients report complete symptom resolution, others report residual range of motion impairments and pain. 10 , 14 Despite reports of a three-phased evolution of the disease (freezing, frozen, and thawing), there exists no strong evidence supporting this kind of subclassification 10 in terms of prognostic or diagnostic value.…”
Section: Introductionmentioning
confidence: 99%
“…In the multifactorial disease frozen shoulder (FS), patients often have shoulder pain with limited active and passive mobility of the shoulder ( 1 ). The prevalence of frozen shoulder ranges from 2 to 5%, and most cases occur between the ages of 40 and 65 years ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%